2010
DOI: 10.1002/hyp.7604
|View full text |Cite
|
Sign up to set email alerts
|

Suspended‐sediment sources in an urban watershed, Northeast Branch Anacostia River, Maryland

Abstract: Abstract:Fine sediment sources were characterized by chemical composition in an urban watershed, the Northeast Branch Anacostia River, which drains to the Chesapeake Bay. Concentrations of 63 elements and two radionuclides were measured in possible land-based sediment sources and suspended sediment collected from the water column at the watershed outlet during storm events. These tracer concentrations were used to determine the relative quantity of suspended sediment contributed by each source. Although this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Many of the streams in this watershed have high sediment loads and are listed as impaired under the Total Maximum Daily Load (TMDL) program (US Environmental Protection Agency ). Mineral sediment source tracking studies suggest that the majority (58% annual average) of suspended sediment in the North Branch Anacostia River, an urban watershed, derives from stream banks, with the remainder coming from street residue (13%) and uplands (30%) (Devereux et al ). That finding is consistent with the ubiquity of stream incision (often reaching up to several meters) in the Chesapeake Bay watershed.…”
Section: Sediment Source Tracking In the Chesapeake Bay Watershedmentioning
confidence: 99%
“…Many of the streams in this watershed have high sediment loads and are listed as impaired under the Total Maximum Daily Load (TMDL) program (US Environmental Protection Agency ). Mineral sediment source tracking studies suggest that the majority (58% annual average) of suspended sediment in the North Branch Anacostia River, an urban watershed, derives from stream banks, with the remainder coming from street residue (13%) and uplands (30%) (Devereux et al ). That finding is consistent with the ubiquity of stream incision (often reaching up to several meters) in the Chesapeake Bay watershed.…”
Section: Sediment Source Tracking In the Chesapeake Bay Watershedmentioning
confidence: 99%
“…In addition to modeling and monitoring studies, the sediment fingerprinting technique was shown to provide a powerful tool to identify sediment sources in Brazil (Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ; Minella, Merten, Reichert, & dos Santos, ; Minella, Merten, Walling, & Reichert, ; Minella, Walling, & Merten, , ; Tiecher et al, ; Tiecher, Caner, et al, ; Tiecher, Caner, Minella, & dos Santos, ; Tiecher, Caner, Minella, Bender, & dos Santos, ; Tiecher, Minella, et al, ) and elsewhere in the world, such as in France (Foucher et al, ; Legout et al, ; Navratil, Evrard, Esteves, Legout, et al, ; Poulenard et al, ), Mexico (Evrard et al, ), South Africa (Foster, Boardman, & Keay‐Bright, ), Zambia (Walling, Collins, Sichingabula, & GJL, ), Canada (Barthod et al, ; Koiter et al, ; Stone, Collins, Silins, Emelko, & Zhang, ), United States (Devereux, Prestegaard, Needelman, & Gellis, ), United Kingdom (Collins, Walling, Webb, & King, ; Pulley, Foster, & Antunes, ; Smith & Blake, ), Spain (Brosinsky, Foerster, Segl, & Kaufmann, ), Luxemburg (Martínez‐Carreras et al, ), Turkey (D'Haen et al, ), Tunisia (Ben Slimane et al, ), Iran (Haddadchi, Nosrati, & Ahmadi, ), and Australia (Laceby, McMahon, Evrard, & Olley, ; Olley, Burton, Smolders, Pantus, & Pietsch, ; Wilkinson, Hancock, Bartley, Hawdon, & Keen, ). Therefore, the objective of the current study is to quantify the contribution of sources supplying sediment to the river in a catchment characterized by the widespread implementation of NT since the 1990s in Southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Many different properties have been considered to discriminate potential sediment sources in catchments, such as sediment colour (Poulenard et al ., ), mineral magnetism (Walden et al ., ), environmental radionuclides (Lim et al ., ), geochemical composition (Carter et al ., ), stable isotopes (Bai et al ., ), rare earth elements (Morton, ) and particle size (Stone & Saunderson, ). The behaviour of each tracer in the erosion and transport process must be conservative (Devereux et al ., ), and usually more than one tracer is used (composite fingerprint) for better discrimination of a wide range of potential sources (Collins & Walling, ; Zhang & Liu, ). After establishing the composite fingerprints, the importance of different potential sources can be assessed by the subsequent application of a multivariate mixing model (Carter et al ., ; Nosrati et al ., ; Franz et al ., ; Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%